(untitled) (Training and Practice : Journal of Educational Sciences, 2025)
The development of educational methodology in higher education courses in national security and counter-terrorism has achieved significant changes in recent decades. In the 20th century, these fields typically used closed methods not accessible to the public, whereas today they have increasingly become open systems integrating multidisciplinary approaches. The aim of this study is to present the methodological elements that help students to develop their specific competences in the field of national security and counter-terrorism. In the Hungarian higher education system, courses in national security and counter-terrorism are primarily offered at the Ludovika University of Public Service, where they have a number of unique features. Creative solutions, the integration of traditional and electronic/online environments, and a practice-oriented approach to teaching are highly important during the education of the field and they are presented in this paper. We are continuously seeking new solutions to improve educational methodologies (interdisciplinary approach, practice-oriented focus), expanding students’ competencies while addressing the needs of the respective fields.